Hypoxia Signaling and Circadian Disruption in and by Pheochromocytoma - Tabebi, Mouna; Söderkvist, Peter; Jensen, Lasse D. (Frontiers in Endocrinology, 2018)
Disruption of the daily (i.e. circadian) rhythms of cell metabolism, proliferation and blood perfusion is a hallmark of many cancer types, perhaps most clearly exemplified by the rare but detrimental pheochromocytomas. These tumors arise from genetic disruption of genes critical for hypoxia signaling, such as von Hippel-Lindau and hypoxia-inducible factor-2 or cellular metabolism, such as succinate dehydrogenase, which in turn impacts on the cellular circadian clock function by interfering with the Bmal1 and/or Clock transcription factors. While pheochromocytomas are often non-malignant, the resulting changes in cellular physiology are coupled to de-regulated production of catecholamines, which in turn disruption circadian blood pressure variation and therefore circadian entrainment of other tissues. In this review we thoroughly discuss the molecular and physiological interplay between hypoxia signaling and the circadian clock in pheochromocytoma, and how this underlies endocrine disruption leading to loss of circadian blood pressure variation in the affected patients. We furthermore discuss potential avenues for targeting these tumor-specific pathophysiological mechanisms therapeutically in the future.